EFFECT OF NANO-ALUMINA ON MICROSTRUCTURE AND MECHANICAL PROPERTIES OF RECYCLED CONCRETE - Kadhium Mohammed, Raeid; Abdel-Hamead, Alaa Aladdin; Mohammed Othman, Farhad (Journal of Engineering and Sustainable Development, 2018)
In this paper, the effect of using recycle mortar as fine aggregate replacement and nano Alumina (Al2O3) powder replaced of cement on the concrete microstructure and their effect on the mechanical properties is investigated. The nano powder was used as additive to replaced (0.5, and 2. 5 wt %) of cement with recycle fine aggregate(RFA) to replacement (10,and 50 wt%) of natural fine aggregate in concrete mixture. The compressive strength and microstructure analysis tests were carried out on the concrete samples. Microstructure analysis tests were conducted using X-Ray Diffraction(XRD), Scanning Electron Microscopy(SEM), and Atomic Force Microscopy(AFM). Results shows that the nano-oxide and recycle aggregate addition leads to different microstructure of concrete. The high specific surface area of nano-oxide causes reduce calcium hydroxide Ca(OH)2 (CH) crystallite in the cement hydration process and the pores structure of calcium silicate hydrated gel lead to products denser and compacted microstructure, also the roughness of concrete surface was reduces which caused enhancement in the compressive strength with the addition of nano- Al2O3